INTERCULTURAL COMMUNICATION CHALLENGES IN DIGITAL COMMUNICATION: A GLOBAL PERSPECTIVE - Loso Judijanto; Vera Aryani (INTERNATIONAL JOURNAL OF SOCIETY REVIEWS, 2025)
Linguistic differences and cultural norms are often a major source of misunderstanding and tension in digital interactions. Language barriers can reduce the effectiveness of information exchange, while differences in etiquette and communication styles can affect the quality of communication and coordination between cultures. Differences in access to technology also contribute to unequal participation in global digital communication. Therefore, concerted efforts are needed from technology providers and international organisations to create platforms that are more inclusive and responsive to cultural diversity. Improved cross-cultural education and digital literacy are key to addressing these challenges and supporting harmonious interactions online.